Brefeldin A Reduces Anchorage-Independent Survival, Cancer Stem Cell Potential and Migration of MDA-MB-231 Human Breast Cancer Cells - Chao-Neng Tseng (Molecules, 2014)
Cancer stem cells (CSCs) are a subset of cancer cells in tumors or established cancer cell lines that can initiate and sustain the growth of tumors in vivo. Cancer stem cells can be enriched in serum-free, suspended cultures that allow the formation of tumorspheres over several days to weeks. Brefeldin A (BFA) is a mycotoxin that induces endoplasmic reticulum (ER) stress in eukaryotic cells. We found that BFA, at sub-microgram per milliliter concentrations, preferentially induced cell death in MDA-MB-231 suspension cultures (EC50: 0.016 µg/mL) compared to adhesion cultures. BFA also effectively inhibited clonogenic activity and the migration and matrix metalloproteinases-9 (MMP-9) activity of MDA-MB-231 cells. Western blotting analysis indicated that the effects of BFA may be mediated by the down-regulation of breast CSC marker CD44 and anti-apoptotic proteins Bcl-2 and Mcl-1, as well as the reversal of epithelial-mesenchymal transition. Furthermore, BFA also displayed selective cytotoxicity toward suspended MDA-MB-468 cells, and suppressed tumorsphere formation in T47D and MDA-MB-453 cells, suggesting that BFA may be effective against breast cancer cells of various phenotypes.